The effect of Katuk leaf to breastfeeding mother: a literature review - Alfonsus Zeus Suryawan; Nicholas Renata Lazarosony (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2021)
Indonesians traditionally consume Katuk (Sauropus androgynus (L) Merr) leaf to treat various diseases, improve weight loss, and as vegetable dishes. Sauropus androgynus, also known as a medicinal plant with high antioxidant potential, is also traditionally utilized to increase breastmilk production during lactation. Lactation is a process of milk synthesis and secretion, in which Prolactin responsible for the synthesis of breastmilk. Recent studies have proven that Katuk leaf extract can increase the breastfeeding quality and prolactin level in breastfeeding women. This article provides a brief summary of evidence supporting the use of Katuk leaf to improve breastmilk production in breastfeeding mothers.